ROBOTICS AT HOME WITH RASPBERRY PI PICO build autonomous robots with the versatile low cost Raspberry Pi Pico controller and Python. - Staple, Danny (PACKT PUBLISHING LIMITED, 2023)
Design, build, and program a mobile robot platform while gaining an understanding of the Raspberry Pi Pico, Free CAD, and robot sensors using Python to code, Bluetooth to connect & smartphone to control your projects Key Features Gain in depth knowledge of robotics with easy-to-follow instructions Build a rover platform designed for experimentation and extension Enhance your robot building skills through planning, building, and coding Purchase of the print or Kindle book includes a free PDF eBook Book Description The field of robotics is expanding, and this is the perfect time to learn how to create robots at home for different purposes. This book will help you take your first steps in planning, building, and programming a robot with Raspberry Pi Pico, an impressive controller bursting with I/O capabilities. After a quick tour of Pico, you'll begin designing a robot chassis in 3D CAD. With easy-to-follow instructions, shopping lists, and plans, you'll start building the robot. Further, you'll add simple sensors and outputs to extend the robot, reinforce your design skills, and build your knowledge in programming with CircuitPython. You'll also learn about interactions with electronics, standard robotics algorithms, and the discipline and process for building robots. Moving forward, you'll learn how to add more complicated sensors and robotic behaviors, with increasing complexity levels, giving you hands-on experience. You'll learn about Raspberry Pi Pico's excellent features, such as PIO, adding capabilities such as avoiding walls, detecting movement, and compass headings. You'll combine these with Bluetooth BLE for seeing sensor data and remotely controlling your robot with a smartphone. Finally, you'll program the robot to find its location in an arena. By the end of this book, you'll have built a robot at home, and be well equipped to build more with different levels of complexity. What you will learn Interface Raspberry Pi Pico with motors to move parts Design in 3D CAD with Free CAD Build a simple robot and extend it for more complex projects Interface Raspberry Pi Pico with sensors and Bluetooth BLE Visualize robot data with Matplotlib Gain an understanding of robotics algorithms on Pico for smart behavior Who this book is for This book is for beginner robot makers, keen hobbyists, technical enthusiasts, developers and STEM teachers who want to build robots at home. Prior knowledge of coding - beginner to intermediate programming, will be helpful.